An Interdisciplinary Perspective from the Earth Scientist's Periodic Table: Similarity and Connection between Geochemistry and Metallurgy. (June 2020) - Sun, Fenglong; Zhao, Zhongwei
Abstract: In 2003, Railsback proposed the Earth Scientist's Periodic Table, which displays a great deal of elemental geology information in accordance with the natural environment of the earth. As an applied science, metallurgy is based on mineral composition and element behavior, that is similar to geochemistry. In this paper, connections and similarities between geology and metallurgy are identified, based on geochemical laws and numerous metallurgical cases. An obvious connection is that simple cations with high and low ionic potential are commonly extracted by hydrometallurgy, while those with intermediate ionic potential are extracted by pyrometallurgy. In addition, element affinity in geology is associated with element migration in metallurgic phases. To be specific, in pyrometallurgy, lithophile elements tend to gather in slags, chalcophile elements prefer the matte phase, siderophile elements are easily absorbed into metal melt, and atmophile elements readily enter the gas phase. Furthermore, in hydrometallurgy, the principles of hard/soft acids and bases (HSABs) offer an explanation of how precipitation and dissolution occur in different solutions, especially for fluoride and chloride. This article provides many metallurgical examples based on the principles of geochemistry to verify these similarities and connections.